Higher Social Rejection Sensitivity in Opioid-Dependent Patients Is Related to Smaller Insula Gray Matter Volume: A Voxel-Based Morphometric Study. Issue 11 (10th December 2019) - Bach, Patrick; Frischknecht, Ulrich; Klinkowski, Svenja; Bungert, Melanie; Karl, Damian; Vollmert, Christian; Vollstädt-Klein, Sabine; Lis, Stefanie; Kiefer, Falk; Hermann, Derik
Abstract: Opioid-dependent patients are highly sensitized to negative social feedback, and increased social rejection sensitivity was linked to adverse treatment outcome, but its neurobiological underpinnings have not been understood yet. The present study investigated gray matter (GM) volume differences between 19 opioid maintenance treatment (OMT) patients and 20 healthy controls using magnetic resonance imaging and voxel-based morphometry. Associations of GM volumes with subjective feelings of exclusion and inclusion during a social ostracism (Cyberball) paradigm, with rejection sensitivity, social interaction anxiety and social phobia were explored. OMT patients displayed smaller GM volume in the bilateral insula and inferior frontal gyri. Psychometric and task data showed that patients reported significantly higher rejection sensitivity, social anxiety and social phobia scores and felt more excluded and less included during the social ostracism paradigm. Smaller GM volume in the insula was associated with higher subjective exclusion, lower subjective inclusion and higher rejection sensitivity, social anxiety and social phobia scores. Findings indicate that structural deficits in emotion- and anxiety-processing brain regions in OMT patients are associated with increased social rejection sensitivity. As social rejection is a potential trigger for relapse, patients might benefit from therapeutic strategies that promote social integration.